High technology vs human value: intention to reduce road accident cases via user experience (UX) and user interface (UI) - Abdul Kadir, Andi Nursyuhada; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal; Ramli, Saiful Hasley; Abdullah, Jusang (Malaysian Institute of Road Safety Research, 2018)
As the evolvement of technology rapidly increases in our daily life, indirectly it impacts the human value. Because of that, the implementation of User Experience (UX) and User Interface (UI) plays an important role in creating a better future. It is not just for styling purpose, but more to life contribution, especially in intention to reduce road accident cases. The purpose of this study is to investigate the perception of road user on how technology could affect human value. This study uses Document review and structured observation for general understanding on Road Accident Cases, User Experience (UX) and User Interface (UI). Then, it uses the survey for road user to identify their perception on this main theme. 50 road users randomly selected as participants in this research. 86% of the respondents agreed with a great implementation of User Experience (UX) and User Interface (UI) understanding could help the intention to reduce road accident cases while 14% feel uncertainty on how User Experience (UX) and User Interface (UI) will be implemented well. The results lead towards the important of User Experience (UX) and User Interface (UI) in balancing high technology and human value. After the introduction of the background problem, this paper describes the research methodology before presenting the results. This preliminary study enhances users’ knowledge, important area that needs to focus to secure human value even with usability of high technology.